Study on Optical Properties of Micro-Modulator Through $Z$ -Scanning Method - X. B. Jiao; S. Xue; Y. F. Shen; M. Y. Chen; Z. W. Liu (IEEE Photonics Journal)
Stokes polarimeters and scanning slit optical beam profilers are used to measure the polarization properties and optical spot intensities of a laser beam, which go through the micromodulator by the $Z$ -scanning method. The polarization properties of a $S$ -polarized and a $P$ -polarized light are researched. The optical intensities of laser beam are obtained for $S$ -polarized light by the $Z$ -scanning method. The results show that the groove films can affect the polarization properties of the $P$ -polarized light but do not change the polarization properties of the $S$ -polarized light. The optical spot intensity of $S$ -polarized light can be changed with the help of groove films as the scattering effect.